Analisis Pola Tanam dan Respon Lingkungan terhadap Produktivitas Tanaman Hortikultura Kelompok Tani Subur Makmur Desa Birayang Timur - Nur Inayah Ariyani; Fahrina Roli (Agroekotek View, 2026)
This study aims to analyze cropping patterns and environmental responses to horticultural crop productivity in the Subur Makmur Farmers Group in East Birayang Village, South Batang Alai District. This study was conducted using a descriptive survey method with an evaluative approach. Cropping pattern data were collected through farmer interviews, while environmental data in the form of air temperature, humidity, and rainfall were obtained from the Meteorology, Climatology, and Geophysics Agency (BMKG). The analysis was conducted descriptively by comparing actual environmental conditions with the physiological needs of chili and tomato plants. The results showed that farmers implemented a monoculture cropping pattern of chili and tomato throughout the year. Climatic conditions in the study area have an air temperature of 26–32°C, relative humidity of 65–85%, and annual rainfall of 2,000–3,000 mm, with monthly rainfall ranging from 50.0–309.5 mm. The optimum rainfall range (100–200 mm/month) only occurs in several months of the year, so land suitability is temporal. Fluctuations in rainfall have the potential to affect plant physiological responses and cause variations in productivity. Therefore, adjusting planting times and water management based on monthly rainfall distribution is necessary to increase horticultural productivity.